Research on Vehicle-Network Harmonic Coupling Characteristic and Onboard Suppression Strategy - Wenguang LUO; Gang FU (机车电传动)
In order to solve the problem of vehicle-network matching caused by vehicle-network harmonic coupling economically and effectively, the harmonic characteristics of the current of the AC network side and the relationship of the voltage harmonic of the traction network were analyzed, and some basic conclusions and rules with guiding effect were obtained. Then, the vehicle harmonic suppression strategy based on PR control and state observation was proposed, and through the line operation test, the strategy was proved could effectively suppress the resonance of the train network, achieving the excellent performance that the total harmonic distortion rate of the train network side current was 0.5%, and the equivalent interference current was 1A, which ensured the safe and reliable operation of the train network system.